Ternary nanocomposites of reduced graphene oxide, polyaniline and hexaniobate: hierarchical architecture and high polaron formation - Claudio H. B. Silva; Maria Iliut; Christopher Muryn; Christian Berger; Zachary Coldrick; Vera R. L. Constantino; Marcia L. A. Temperini; Aravind Vijayaraghavan (Beilstein Journal of Nanotechnology, 2018)
Nanostructured systems, such as nanocomposites, are potential materials for usage in different fields since synergistic effects of their components at the nanoscale domain may improve physical/chemical properties when compared to individual phases. We report here the preparation and characterisation of a new nanocomposite composed of polyaniline (PANI), reduced graphene oxide (rGO) and hexaniobate (hexNb) nanoscrolls. Atomic force microscopy images show an interesting architecture of rGO flakes coated with PANI and decorated by hexNb. Such features are attributed to the high stability of the rGO flakes prepared at room temperature. Detailed characterisation by X-ray photoelectron and Raman spectroscopies indicates an intermediate reduction degree for the rGO component and high doping degree of the PANI chains compared to the neat polymer. The latter feature can be attributed to cooperative effects of PANI chains with rGO flakes and hexNb nanoscrolls, which promote conformational changes of the polymer backbone (secondary doping). Spectroscopic and electrochemistry data indicate a synergetic effect on the ternary nanocomposite, which is attributed to interactions between the components resulting from the morphological aspects. Therefore, the new nanocomposite presents promising properties for development of new materials in the film form on substrates for sensing or corrosion protection for example.